Associations of Urine Epidermal Growth Factor With Kidney and Cardiovascular Outcomes in Individuals With CKD in SPRINT - Merve Postalcioglu; Ronit Katz; Simon B. Ascher; Trenton Hall; Pranav S. Garimella; Stein I. Hallan; Joachim H. Ix; Michael G. Shlipak (Kidney International Reports)
Introduction: Urine epidermal growth factor (uEGF) has been found to be inversely associated with kidney function loss, whereas its associations with cardiovascular disease (CVD) and mortality have not been studied. Methods: We measured baseline uEGF levels among 2346 Systolic Blood Pressure Intervention Trial (SPRINT) participants with an estimated glomerular filtration rate (eGFR) < 60 ml/min per 1.73 m2. A linear mixed-effects model was used to investigate the associations of uEGF with the annual eGFR change; Cox proportional hazards regression models were used to analyze its associations with the ≥30% eGFR decline, CVD, and all-cause mortality outcomes. To account for the competing risk of death, the Fine and Gray method was utilized for acute kidney injury (AKI) and end-stage kidney disease (ESKD) outcomes. Results: At baseline, the study participants had mean age of 73 ± 9 years, mean eGFR of 46 ± 11 ml/min per 1.73 m2, and median urine albumin-to-creatinine ratio (UACR) of 15 mg/g (interquartile range: 7–49). In the multivariable-adjusted analysis including baseline urine albumin and eGFR, each 50% lower uEGF concentration was associated with 0.74% (95% confidence interval [CI]: 0.29–1.19) per year faster decline in eGFR and 1.17 times higher risk of ≥30% eGFR decline (95% CI: 1.00–1.36). Lower uEGF concentrations were found to be associated with increased risks of ESKD, AKI, CVD, and all-cause mortality; however, these associations did not reach statistical significance when the models were controlled for baseline urine albumin and eGFR. Conclusion: Among hypertensive adults with chronic kidney disease (CKD), lower baseline uEGF concentration was associated with faster eGFR decline independent of baseline albuminuria and eGFR; but not with ESKD, AKI, CVD, and all-cause mortality.